A plane-based calibration procedure for the 3D analysis of video recordings in discus throwing during competition - Drenk, V. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Standard procedures for the calibration for 3D video measurements in sports biomechanics are the recording of a spatial calibration frame or the wand calibration. Both methods require access to the competition site, which often is not allowed in international championships. Therefore, alternative calibration routines are needed that utilize the geometric conditions of the competition site. For the calibration of 3D video recordings in discus throwing a new method is introduced. It is based solely on given coordinates of spatial control points in the background and the known interior camera parameters. After introducing the solution steps, the method is validated by comparing it to established standard methods using model data. The applicability of this method is demonstrated by analysing discus competition recordings.